APPLICATION OF DKV LEARNING TO INCREASE STUDENT CREATIVITY - Rizki Wiji Nugroho; Dyan Evita Santi (International Conference on Humanity Education and Society (ICHES), 2023)
The industrial 5.0 is a concept that has fundamentally changed the way we live, work and relate to one another. Where creativity is needed in the industrial era 5.0 so that Communication Design learning is needed to increase creativity. Industry 5.0 is closely related to technology and culture. Visual Communication Design and animation is a branch of science that explores high creativity. conveying of messages, ideas or ideas that are manifested visually so that they can have an effect on those who witness them. Universities in Indonesia are currently opening many DKV departments or study programs with animation funds, this is based on the enthusiasm of the public to see career opportunities in the world of creative industries. Visual communication design